2020
DOI: 10.1093/mnras/staa2443
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical models: source-tailored or generic?

Abstract: Physicochemical models can be powerful tools to trace the chemical evolution of a protostellar system and allow to constrain its physical conditions at formation. The aim of this work is to assess whether source-tailored modelling is needed to explain the observed molecular abundances around young, low-mass protostars or if, and to what extent, generic models can improve our understanding of the chemistry in the earliest stages of star formation. The physical conditions and the abundances of simple, most abund… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(20 citation statements)
references
References 96 publications
0
20
0
Order By: Relevance
“…Drozdovskaya et al (2016) found a higher value of 3.7 × 10 −6 at the end of the prestellar phase, when taking into account reaction-diffusion competition. Different physical conditions and timescales during the precollapse phase could also explain the different initial abundances obtained for methanol (Kulterer et al 2020). The total methanol abundance in our model does not evolve significantly during the disk formation and cannot be enhanced as methanol is already formed abundantly in the cold and dense core.…”
Section: Comparison To 2d Semi-analytical Modelsmentioning
confidence: 72%
“…Drozdovskaya et al (2016) found a higher value of 3.7 × 10 −6 at the end of the prestellar phase, when taking into account reaction-diffusion competition. Different physical conditions and timescales during the precollapse phase could also explain the different initial abundances obtained for methanol (Kulterer et al 2020). The total methanol abundance in our model does not evolve significantly during the disk formation and cannot be enhanced as methanol is already formed abundantly in the cold and dense core.…”
Section: Comparison To 2d Semi-analytical Modelsmentioning
confidence: 72%
“…These core ages are common choices for modelling the prestellar phase in physicochemical models. 40 The boosted abstraction scheme of Model 2B leads to a very high CH 2 DOH/CH 3 OD ratio at 10 K and the youngest considered core age of 10 5 yr (∼ 60 compared to 11 at 3 × 10 5 yr). This indicates that a short, cold, prestellar core stage can lead to a very high CH 2 DOH/CH 3 OD ratio and that this value can be considered an upper limit.…”
Section: Ch 2 Doh/ch 3 Od Ratiomentioning
confidence: 93%
“…The physical model is representative of a typical prestellar core. 39,40 The core age of the fiducial model, t core , is assumed to be 3 × 10 5 yr. 40 The dust and gas temperatures (T dust ) are assumed to be the same, and values of 10, 15, 20, 25, and 30 K are considered. The values for the gas density n H = 4 × 10 4 cm −3 and the cosmic ray ionization rate ζ CR = 5 × 10 −17 s −1 remain the same for all discussed modelling runs with the fiducial physical model.…”
Section: Physical Modelmentioning
confidence: 99%
See 2 more Smart Citations